Primary immunodeficiencies: 2009 update. - Notarangelo, L; Fischer, A; Geha, R; Casanova, J; Chapel, H; Conley, M; Cunningham-Rundles, C; Etzioni, A; Hammartröm, L; Nonoyama, S; Ochs, H; Puck, J; et al. (2009)
More than 50 years after Ogdeon Bruton's discovery of congenital agammaglobulinemia, human primary immunodeficiencies (PIDs) continue to unravel novel molecular and cellular mechanisms that govern development and function of the human immune system. This report provides the updated classification of PIDs that has been compiled by the International Union of Immunological Societies Expert Committee on Primary Immunodeficiencies after its biannual meeting in Dublin, Ireland, in June 2009. Since the appearance of the last classification in 2007, novel forms of PID have been discovered, and additional pathophysiology mechanisms that account for PID in human beings have been unraveled. Careful analysis and prompt recognition of these disorders is essential to prompt effective forms of treatment and thus to improve survival and quality of life in patients affected with PIDs.